Analisis Kekasaran dan Kepresisian Hasil Surface Grinding pada Mesin Okamoto Grind-X ACC84ST Dengan Material DIN CK-45 - Andhy Rinanto; Hoedi Prasetyo; Agus Kurniawan; Baruna Arya Putra W; Bobby Muhammad R; Cahyanto Onky S; Nikolaus Alun Prapanca H (Universitas Muhammadiyah Yogyakarta, 2020)
Surface grinding is the finishing proses needs high smoothness and precision. The main demands from this process is precise, roughness, and not burnt. This analyze is made to know the most influential variable for roughness and precision of a product. This analysis is also carried out to determine roughness and precision that can be achieved using the Okamoto Grind-X ACC84ST machine. Variables that used for this analyze are depth of cut, feeding, and cycle per feed. Every variable has three level. DIN CK-45 material is selected to be specimen because it is usually used by manufacturing and automotive industrial to make a main product. Taguchi method is used to reduce time and amount trial. Experiment replication is done to get more accurate data. The most influential variable for roughness is cycle per feed, while the most influential variable for precision is depth of cut. The roughness that can be achieved using the Okamoto Grind-X ACC84ST machine is in the range of 0,075 μm (N3) to 0,175 μm (N4). Size deviations that occurred in this study ranged from -0,007 mm to 0,005 mm.